Supporting Students and Young Professionals in Environmental and Occupational Health, Safety, Science, and Policy-Related Graduate Programs. - Shendell, Derek G.; Shah, Nimit N.; Jones, Laura E. (Journal of Environmental Health, 2020)
This 2017-2019 project started with a systematic assessment of three independent environmental and occupational healthrelated doctoral (PhD) programs, which are sponsored by different agencies, institutes, and schools within Rutgers Biomedical and Health Sciences at Rutgers, The State University of New Jersey: Exposure Science, Toxicology, and Environmental Health. In addition, we examined other graduate and undergraduate environment-related schools, departments, divisions, and institutes with degree programs (majors and minors) and certificate programs at Rutgers. Then, we conducted a survey of students. Data collected can result in enhancements to connections between entities, with multiple potential benefits. For example, for Rutgers School of Public Health, data can inform efforts to increase student applications to both master's and doctoral programs, as well as increase faculty participation in teaching and student advising. The project should result in more qualified student applications from students in their final year of master's programs. Subsequently, acceptances into and matriculations from PhD programs should also increase. Overall, this approach should provide more continuity of scholarship at schools, institutes and/or other environmental programs at Rutgers. In summary, this project's data can help support positive yet complex relationships across engaged entities at Rutgers and inform other U.S. environmental health programs.